2021
DOI: 10.1111/bld.12371
|View full text |Cite
|
Sign up to set email alerts
|

Talking with parents of children with learning disabilities: Parents’ ideas about the Circle of Security parenting programme

Abstract: Accessible Summary The Circle of Security Parenting (COS‐P) programme can be helpful for some parents of children with learning disabilities to think about their relationship with their child. Parenting a child with learning disabilities is different, and COS‐P can highlight this difference. This can feel painful for parents and may stop them engaging with the programme. Abstract BackgroundBackground: The promotion of secure attachment relationships in childhood leads to better outcomes in later life (Brit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…It is significant that among the blind and visually impaired (age [16][17][18], more than half consider themselves to be computer users. Everyone without exception is planning to use a computer in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is significant that among the blind and visually impaired (age [16][17][18], more than half consider themselves to be computer users. Everyone without exception is planning to use a computer in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The general problems of integration of people with disabilities into society are considered in the works of different social scientists and psychologists [1], [6][7][8][9][10][11][12][13], [16][17][18], [20][21][22][23][24], [29]. Much attention is paid to problems generated not by specific restrictions on life, but by special socio-cultural status of the disabled.…”
Section: Methodsmentioning
confidence: 99%
“…A qualitative methodology was employed to explore parents' experiences of participating in a feeding clinic. Using interview methods to gain an understanding of service users' experience of group interventions has been noted in the learning disability literature (Dixon‐Ibarra et al, 2018; Muddle et al, 2020). The interviews were designed to promote open discussion and reflections on their experiences (Ogden, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to dialogue with educators, parents also benefit from spending time interacting with other parents (Muddle et al, 2022). In the remote learning environment, educators can encourage ties between families of students in remote schools through asynchronous discussion boards (Valcarlos et al, 2020).…”
Section: Sincerely ____________ Phone Number Email Addressmentioning
confidence: 99%
“…Some families may benefit from synchronous options for interaction in addition to or instead of asynchronous discussions. Muddle et al (2022) found that parents of children with LD benefited from group discussion in a program designed to build secure attachment to their children. Teachers can create their own topics for monthly discussion based on the expressed needs of their families.…”
Section: Sincerely ____________ Phone Number Email Addressmentioning
confidence: 99%